2013
DOI: 10.1007/s10482-013-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

An Lrp-type transcriptional regulator controls expression of the Bacillus subtilis chromate transporter

Abstract: The Bacillus subtilis strain 168 genome contains the chr3N-chr3C genes encoding the Chr3N/Chr3C protein pair of the chromate ion transporter (CHR) superfamily. Chr3N/Chr3C confers chromate resistance in Escherichia coli only when both proteins are expressed. Upstream of chr3N is the chrS gene encoding ChrS, a protein with homology to the Lrp/AsnC family of transcriptional regulators. When the chrS-chr3N-chr3C gene cluster was transferred to E. coli, a diminished level of chromate resistance was observed, as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…B. subtilis is itself moderately Cr-tolerant as it tolerates time-limited exposure to Cr(VI) in sub-millimolar concentrations and can resume the growth after the concentration of the toxic metal decreases ( Garbisu et al, 1998 ). B. subtilis harbors an innate Cr efflux system in its genome, consisting of two SCHR chromate transporters ywrB ( chr3N ) and ywrA ( chr3C ), expression of which is regulated by a Cr-responsive Lrp-type regulator ChrS ( Díaz-Magaña et al, 2009 ; Aguilar-Barajas et al, 2013 ). In contrast, the Cr-resistant NCr1a strain likely harbors only chromosomally encoded putative LCHR chromate transporter ChrA with no regulator sequences detected in the close vicinity of its promoter region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…B. subtilis is itself moderately Cr-tolerant as it tolerates time-limited exposure to Cr(VI) in sub-millimolar concentrations and can resume the growth after the concentration of the toxic metal decreases ( Garbisu et al, 1998 ). B. subtilis harbors an innate Cr efflux system in its genome, consisting of two SCHR chromate transporters ywrB ( chr3N ) and ywrA ( chr3C ), expression of which is regulated by a Cr-responsive Lrp-type regulator ChrS ( Díaz-Magaña et al, 2009 ; Aguilar-Barajas et al, 2013 ). In contrast, the Cr-resistant NCr1a strain likely harbors only chromosomally encoded putative LCHR chromate transporter ChrA with no regulator sequences detected in the close vicinity of its promoter region.…”
Section: Resultsmentioning
confidence: 99%
“…Our experimental hypothesis was that the Cr efflux pump of the NCr1a strain, ChrA, may be more effective than its PY79 counterpart, YwrBA. This seemed to be supported by the fact that the two efflux pumps belong to divergent families within the CHR superfamily, that their genetic determinants are differently organized in the genome, and their expression is dissimilarly regulated ( Díaz-Pérez et al, 2007 ; Aguilar-Barajas et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the transcriptional levels of brnQ were enhanced in lrp deletion strain and reduced in lrp overexpression strains, and EMSA results confirmed that Lrp indirectly regulate BrnQ expression. Previously, Lrp has been demonstrated to be involved in the regulations of chromate transporter, chromosome condensation, sporulation and amino acid metabolism in B. subtilis [ 23 , [30] , [31] , [32] ]. Although it was reported that AzlB, a Lrp-like protein, could regulate the distribution of BCAAs in B. subtilis , this regulation mechanism has not been well studied [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…mediterranei and incorporated into its cellular interior [30]. There is a previous assay about a bacterial heavy-metal resistance system controlled by an Lrp-type transcriptional regulator in Bacillus subtilis [56]. For this reason, why not think that these metals may be acting as ligands binding to the Lrp, inducing conformational changes in the structure that may affect the DNA binding by changing the DNA binding affinity?…”
Section: Characterization Of Lrp Promoter Region Using β-Galactosidase As a Reporter Genementioning
confidence: 99%